The impact of the Livelihood Facilities of the Consortium of Humanitarian Agencies (CHA) on the Life stage of IDPs - Selvarajan, P. (National Centre for Advanced Studies, Sri Lanka., 2009)
This study investigates how far the Livelihood support facilities given by the Consortium of Humanitarian Agencies (CHA) would be useful to its beneficiaries. CHA is an association of agencies working with and supporting the work of NGOs in Sri Lanka through its regional network for the past nine years. They have recently initiated a programme to provide some facilities to Internally Displaced People (IDPs). The analysis of influence and constraints of CHA which affect people in the “Kanthinagar” locality in Vavuniya district is discussed in this paper. Among the 117 families in "Kanthinagar", a sample of 50 was randomly selected for the study. A structured questionnaire was designed to collect data. Other information was collected through observation and interviews. The findings show that lack of Educational facilities and improper shelter planning are major problems. The study recommends re planning their budget and proper advice with periodic guidance to improve the life status of beneficiaries.
Keywords: Internally Displaced People (IDPs); Livelihood facilities; Non- Government Organizations.